Gangguan Depresi Mayor: Mini Review - Hadi, Indriono; Wijayati, Fitri; Usman, Reni Devianti; Rosyanti, Lilin (Poltekkes Kemenkes Kendari, 2017)
Depression is a condition of a person feeling sad, disappointed when experiencing a change, loss, failure and becoming pathological when unable to adapt. Depression is a condition that affects a person affectively, physiologically, cognitively and behaviorally thus changing the usual patterns and responses. Major Depressive Disorder is a heterogeneous disease characterized by feelings of depression, anhedonia, changes in cognitive function, changes in sleep, changes in appetite, guilt that occur over two weeks, described with a loss of interest or pleasure in the usual activity and is a disease with neurobiological consequences involving structural, functional and molecular changes in some areas of the brain. Maladaptive neural responses, social, psychological, and physiological rejections interact with each other with other susceptibility factors, such as a history of depression, life stress levels, genetic factors, will increase a person's susceptibility to depression.